A Review on Pharmacological and Therapeutic Aspect of Shirishadi Agada w.s.r. Vishachikitsa (International Journal of Ayurveda and Pharma Research, 2023)
In Agadtantra many Jangam (animal poison) and Sthawar visha (plant poisoning) are described and in treatment of Visha many Agada are described. Agad means drug or formulation of drug which act against poisons or neutralize the poisoning effects. Keet visha (insect bite) is one of the common poisoning in Jangam visha. In Ayurvedic Samhitas many Agada formulations are described in treatment of Keet visha. Shirishadi Agada is mentioned in treatment of Keet visha (insect bite), Sarp (snake bite), Luta (spider), Mushak (rat poison) and Vruschik visha (scorpion bite) in Ashtang hridayam in Uttarsthana. Shirishadi Agad is herbal formulation contains Shirish, Pippali and Arka. This review is for collective information about therapeutic and pharmacological action of Shirishadi Agada.